Mental health/illness and prisons as place: frontline clinicians’ perspectives of mental health work in a penal setting - Wright, Nicola; Jordan, Melanie; Kane, Eddie (Elsevier, 2014)
This article takes mental health and prisons as its two foci. It explores the links between social and structural aspects of the penal setting, the provision of mental healthcare in prisons, and mental health work in this environment. This analysis utilises qualitative interview data from prison-based fieldwork undertaken in Her Majesty׳s Prison Service, England. Two themes are discussed: (1) the desire and practicalities of doing mental health work and (2) prison staff as mental health work allies. Concepts covered include equivalence, training, ownership, informal communication, mental health knowledge, service gatekeepers, case identification, and unmet need. Implications for practice are (1) the mental health knowledge and understanding of prison wing staff could be appraised and developed to improve mental healthcare and address unmet need. Their role as observers and gatekeepers could be considered. (2) The realities of frontline mental health work for clinicians in the penal environment should be embraced and used to produce and implement improved policy and practice guidance, which is in better accord with the actuality of the context – both socially and structurally.